(untitled) (Altre Modernità, 2016)
This essay applies the crónica del desincanto theory to Bruno Morchio’s crime fiction through a comparison between the first three novels of the Bacci Pagano’s series and the first three novels of the Pepe Carvalho sagas, by Manuel Vázquez Montalbán. The comparison aims also to introduce to Italy the notion of disincanto as a critical perspective for the study of crime fictions and for the interpretation of the contemporary Italian society.